Social media in Swedish foreign policy - Broś, Natalia (Political Preferences, 2017)
The article discusses the use of social media in Sweden's foreign policy, which, as part of public diplomacy, complements the diplomatic channel by reaching a wider audience - the international public. The starting point for the discussion was the presentation of Sweden's foreign policy concept, its normative character where human rights, peace diplomacy, sustainable development or feminism are key values and set the course of action. In Swedish case the nation brand and the associated categories of credibility and reputation, which are sources of power (soft power), are also an important aspect used for effective foreign policy. The analysis of contents of the three key profiles, allowed to present the strategy of using social media in Sweden's foreign policy, to observe what issues are being addressed in them, the relationships between the official diplomatic discourse and the less formal social media content. Key words: Sweden, public diplomacy, foreign policy, social media